Application of School-Based Quality Management in Improving Educational Quality - Memik Nor Fadilah; Asih Umi Kholifah; Titik Haryati (Global Action and Education for Society, 2026)
This study investigates the implementation of School-Based Quality Management (SBQM) at SD Negeri Gunungpati 03, Semarang City, as a strategy to enhance the quality of primary education in Indonesia. Employing a qualitative case study approach, data were collected through in-depth interviews, direct observations, and documentation, and were analysed using the Miles and Huberman model with triangulation to ensure validity. The findings reveal that SBQM at the school level fosters participatory planning, localized curriculum development, continuous teacher professional development, transparent resource management, and increased community engagement. These efforts have contributed to improved learning outcomes, strengthened teacher competencies, and a more inclusive learning environment. However, significant challenges remain, particularly related to limited financial resources and inadequate technological infrastructure. Strong leadership, stakeholder involvement, and adaptive strategies have proven crucial in overcoming these barriers. The study offers practical insights for educational policymakers and school leaders seeking to implement effective, context-sensitive quality management in similar educational settings.